HOAXES AND ECHO CHAMBERS: THE PHENOMENON OF CONFIRMATION BIAS IN THE DIGITAL SPACE - Al-Amin; Lina Affifatusholihah (Adisam Publisher, 2025)
The phenomenon of hoaxes and echo chambers in the digital space is becoming increasingly worrying as social media algorithms that reinforce user confirmation bias continue to develop. This study aims to analyse the patterns of interaction between hoaxes, echo chambers, and confirmation bias, as well as their impact on social polarisation in the post-truth era. Through literature review and analysis of social media comment interactions, it was found that individuals tend to only be exposed to and believe information that aligns with their beliefs, while differing views are often ignored or even rejected. Filter bubble algorithms reinforce information isolation and create homogeneous echo chambers, allowing hoaxes and misinformation to spread unchallenged. The combination of these three phenomena contributes significantly to social fragmentation, deepens polarisation, and reduces the quality of public discourse. This study emphasises the need to improve digital literacy and algorithm transparency to minimise the negative impact of hoaxes and echo chambers and encourage the creation of an inclusive and dialogic digital space.